Effectiveness of Herbal Extract (Piper retrofractum, Curcuma aeruginosa, and Curcuma zanthorrhiza) as Immunomodulator in Non-Specific Immunity System of Tiger Grouper (Epinephelus fuscoguttatus) against Infection from Vibrio alginolyticus and Vibrio parah - wilis setyati; Subagiyo Subagiyo; Rini Pramesti; Delianis Pringgenies (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2019)
The success of aquaculture is one of the supporting factors in food sustainability, one of such is the aquaculture of tiger grouper (Epinephelus fuscoguttatus). The main issue of tiger grouper (Epinephelus fuscoguttatus) aquaculture is disease infestation caused by viruses, microbes, and fungi (1). One of the technologies to control such infestation is the immunostimulant of non-specific immunity. Traditional herbs such as Piper retrofractum, Curcuma aeruginosa, and Curcuma zanthorrhiza have been proven to enhance the immunity system. This study aims to determine the optimal dosage of herb extract (Piper retrofractum, Curcuma aeruginosa, and Curcuma zanthorrhiza) to strengthen non-specific immunity of tiger grouper (Epinephelus fuscoguttatus), to record data on total leukocyte count and phagocytosis activity in the subject against pathogenic infection from Vibrio alginolyticus and Vibrio parahaemolyticus, and on the side effects of the application of the herbal extracts on meat quality (organoleptic) of tiger grouper (Epinephelus fuscoguttatus)(2). The study was carried out by experimental method using random design with 3 repetitions. The experiment was performed in plastic tanks using flow through system with siphon construction. Steps performed include: Herb sample collection, herb samples extraction, herb extract supplementation into artificial food, dose optimization of herb extract application, challenge test, and side effect test (3). The result shows that treatment with 1% Piper retrofractum, 0.5% Curcuma aeruginosa, and 1% Curcuma zanthorrhiza herb extract increased total leukocyte count and phagocytosis activity in tiger grouper (Epinephelus fuscoguttatus). Organoleptic test of all three treatments indicated similar results, with solid texture and bland flavor. Challenge test against pathogenic infection from V. alginolyticus and V. parahaemolyticus found that the treatment reduced the mortality rate to 0%. Based on the results of this study, Piper retrofractum, Curcuma aeruginosa, and Curcuma zanthorrhiza were proven to be viable immunomodulator on non-specific immunity system in tiger grouper (Epinephelus fuscoguttatus) fish against infection from Vibrio alginolyticus and Vibrio parahaemolyticus.